2022
DOI: 10.1002/adma.202207320
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Suppressed Energetic Disorder in a Chemically Doped Conjugated Polymer

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.202207320.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Hole delocalization results in a spectral redshift of the mid-IR peak (P 1 ) in going from the polaron to higher multipolaron complexes, consistent with the redshift of P 1 observed by Enengl et al, 70 as a function of oxidation potential in the electrochemical doping of P3HT. Our results also account for the red shifts of P 1 with increasing dopant concentration observed for IDT-BT 72 and PBTTT. 73 Interestingly, the P 1 redshift is independent of the ground-state multiplicity.…”
Section: Discussion/conclusionsupporting
confidence: 72%
See 1 more Smart Citation
“…Hole delocalization results in a spectral redshift of the mid-IR peak (P 1 ) in going from the polaron to higher multipolaron complexes, consistent with the redshift of P 1 observed by Enengl et al, 70 as a function of oxidation potential in the electrochemical doping of P3HT. Our results also account for the red shifts of P 1 with increasing dopant concentration observed for IDT-BT 72 and PBTTT. 73 Interestingly, the P 1 redshift is independent of the ground-state multiplicity.…”
Section: Discussion/conclusionsupporting
confidence: 72%
“…A subsequent study by Neusser et al on electrochemically doped P3HT also showed that both polarons and bipolarons coexist at the highest doping levels. A red-shifted P 1 band attributed to bipolarons was also obtained for doped IDT-BT and PBTTT as a function of increasing dopant concentration. Recently, we showed that the redshift measured by Enengl et al is consistent with hole delocalization within a bound bipolaron complex .…”
Section: Introductionmentioning
confidence: 69%
“…More importantly, there is no reported firm evidence about the origin of the observed (limited degree of) molecular arrangements in this polymer. Furthermore, the charge transport mechanism in IDTBT is (generally) believed to be mainly one-dimensional and through the backbone of polymer. ,, This is mainly based on the lack or very limited amount of crystallinity as observed by DSC or GIWAXS , for this polymer. However, it is believed that for the extraordinary high mobility of this polymer, a strong interchain electronic coupling is crucial .…”
mentioning
confidence: 99%
“…The emergence of semiconducting polymers (SCPs) with outstanding charge carrier mobility and without semicrystalline morphology has been a new paradigm in SCP development. IDTBT has been one of the most interesting, with respect to properties, e.g., great solubility and high charge carrier mobility, , and puzzling, regarding the morphology–property relationships, SCPs of this kind. Therefore, the special structural features of this polymer have been extensively investigated. , It is generally believed that the torsion-free backbone of polymer (due to the high torsion barrier between IDT and BT) results in a ribbon-like chain conformation and provides a great intrachain charge transport. ,,,, However, there is a considerable degree of uncertainty in the reported characteristics of the IDTBT microstructure. For instance, while several studies emphasize its amorphous-like structure, ,,, some report a limited degree of crystallinity ,, and there is also reported evidence of remarkable short- and medium-range order and unconventional packing (compared with conventional semicrystalline polymers) .…”
mentioning
confidence: 99%
See 1 more Smart Citation